Differences in Nanostructure and Hydrophobicity of Cicada (Cryptotympana atrata) Forewing Surface with the Distribution of Precipitation - Mingxia Sun; Jiajing Zhang; Gregory S. Watson; Jolanta A. Watson; Dong Han; Aiping Liang (Applied Bionics and Biomechanics)
Although the cicada wing has a variety of functions and the nanostructure and surface properties of many species have been extensively investigated, there are no reports investigating diversity of nanostructures and wetting properties within a single species collected at locations with different rainfall conditions. In this study, the hydrophobicity and nanostructure dimensions of the forewing surface of Cryptotympana atrata were measured, based on specimens collected from 12 distributions with varying precipitation averages in China and Japan. The relationships among hydrophobicity, nanostructures, and precipitation were analyzed, and the adaption of hydrophobic nanostructures under different wet environments is discussed. The precipitation of locations in the years the samples of C. atrata were collected only has an effect on the diameter and spacing of wing surface nanostructure, and the multiple years of precipitation may have an influence on the basic diameter and spacing, as well as the height of protrusions. The rougher the wing surface, the stronger the hydrophobicity which was observed from samples taken where the rainfall conditions of the collection years are high. To our knowledge, this is one special example providing evidence of hydrophobic nanostructures found on a biological surface of a single species which shows adaption for specific wet environments.